2021
DOI: 10.3390/polym13020206
|View full text |Cite
|
Sign up to set email alerts
|

Slippery Liquid-Infused Porous Polymeric Surfaces Based on Natural Oil with Antimicrobial Effect

Abstract: Many polymer materials have found a wide variety of applications in biomedical industries due to their excellent mechanical properties. However, the infections associated with the biofilm formation represent serious problems resulting from the initial bacterial attachment on the polymeric surface. The development of novel slippery liquid-infused porous surfaces (SLIPSs) represents promising method for the biofilm formation prevention. These surfaces are characterized by specific microstructural roughness able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In addition, the fiber topography on the surface of PEICT ENM, revealed by the inset atomic force microscopic (AFM) image of Figure 2A, showed a smaller number of gaps between the nanofibers. Good fibroblast cell adhesion on the PEICT ENM surface was perhaps due to the similar frequency of the nanofiber's average diameter, which helped in providing smoothness in parallel to an interconnected nanofiber network to support fibroblast cell infiltration [4,[26][27][28][29].…”
Section: Morphology Of Peict Enmsmentioning
confidence: 99%
“…In addition, the fiber topography on the surface of PEICT ENM, revealed by the inset atomic force microscopic (AFM) image of Figure 2A, showed a smaller number of gaps between the nanofibers. Good fibroblast cell adhesion on the PEICT ENM surface was perhaps due to the similar frequency of the nanofiber's average diameter, which helped in providing smoothness in parallel to an interconnected nanofiber network to support fibroblast cell infiltration [4,[26][27][28][29].…”
Section: Morphology Of Peict Enmsmentioning
confidence: 99%
“…Rather than attempting to prevent lubricant dehydration, we demonstrated that the inevitable process can in utilized to deliver a payload in the form of Ag NPs, as shown by the in vitro assays at 0.2 wt % compared to previous concentrations of 1 wt %. 13 Other antibacterial reagents that could be incorporated into omniphobic LIS include crystal violet 29 antithrombotic agents, functional lipid NPs, or more organic reagents such as black seed oil 30 or natural antimicrobial oils (carvacrol, thymol, cinnamaldehyde, etc.). Therefore, the multifunctionalization of omniphobic coatings represents a novel avenue for investigation which can utilize pre-existing knowledge from hydrogel and other therapeutic release materials to create tailorable omniphobic organogel coatings.…”
Section: Resultsmentioning
confidence: 99%
“…The report by Mikriukova et al not only demonstrates the excellent sliding properties of SLIPS prepared using rapeseed oil, but also proved the promising future of natural lubricants in this field. Habib et al 143 reported a method of preparing SLIPS using natural black seed oil as lubricant. Black seed oil with superior natural properties and antimicrobial properties contains 32 compounds, the main components being 9-octene (63.04%), linoleic acid (13.48%) and palmitic acid (9.68%).…”
Section: Slips Lubricating Oil Choicementioning
confidence: 99%